Fluctuating molar asymmetry in relation to environmental radioactivity. - Angelopoulou, M V; Vlachou, V; Halazonetis, D J (Arch Oral Biol, 2009)
OBJECTIVE: Fluctuating dental asymmetry is considered a sensitive indicator of environmental stress. We used fluctuating asymmetry of teeth in Greek children to assess the effect of the Chernobyl accident to the Greek population, which received relatively large radiation exposure compared to other European countries. DESIGN: Sixty dental casts were divided into two groups according to date of birth prior to or after the Chernobyl accident. The intercuspal distances of the mandibular first permanent molars were measured with digital calipers. We followed the data analysis procedure proposed by Palmer and Strobeck (2003). RESULTS: Fluctuating asymmetry was found at levels above measurement error in all traits except for the buccal measurement. Overall, there were no significant differences in the fluctuating asymmetry between the two groups, after removal of outliers. CONCLUSIONS: These results suggest that environmental radioactivity from the Chernobyl incident did not significantly affect the symmetry of lower permanent molar intercuspal distances in the specific population, even though increased levels of radionuclides have been reported in teeth and other tissues.
Keywords: Chernobyl Nuclear Accident; Dental Models; Greece; Humans; Mandible; Molar; Odontometry; Radiation Dosage; Radioactive Pollutants; Tooth Crown